2016
DOI: 10.4103/2321-0656.187993
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in India: Bio-socioeconomic determinants

Abstract: Worldwide, stroke is one of the leading causes of mortality. Further, it leads to significant morbidity in the form of residual deficits and disability-adjusted life years. India with its culturally diverse environment and economically developing status presents unique challenges in providing stroke care. Various myths, misconceptions, poor knowledge about stroke, and poor availability of health resources afflict the nation and present barriers in stroke management. A multipronged approach to bring various dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although eight papers met the selection criteria, these included a systematic review (Gheorghe et al, 2018), with only one study relevant to our scoping review (Huffman et al, 2011). A decision was made to exclude the systematic review and include only the relevant study (Huffman et al, 2011), resulting in eight studies being included in the scoping review (Bahuguna et al, 2020; Basu et al, 2015; Chhabra et al, 2019; Gopi et al, 2017; Huffman et al, 2011; Kwatra et al, 2013; Marfatia et al, 2014; Singla & Singla, 2016). Details of the records excluded following full-text screening (with related reasons) are presented in Table S5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although eight papers met the selection criteria, these included a systematic review (Gheorghe et al, 2018), with only one study relevant to our scoping review (Huffman et al, 2011). A decision was made to exclude the systematic review and include only the relevant study (Huffman et al, 2011), resulting in eight studies being included in the scoping review (Bahuguna et al, 2020; Basu et al, 2015; Chhabra et al, 2019; Gopi et al, 2017; Huffman et al, 2011; Kwatra et al, 2013; Marfatia et al, 2014; Singla & Singla, 2016). Details of the records excluded following full-text screening (with related reasons) are presented in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…Each included study met the inclusion criteria, and a summary of their characteristics is provided in Table S6. The studies were characterised by various designs, including cost-of-illness studies (n = 3 [Chhabra et al, 2019; Kwatra et al, 2013; Marfatia et al, 2014]), economic evaluations (n = 2 [Basu et al, 2015; Gopi et al, 2017]), a cross-sectional costing study (n = 1 [Huffman et al, 2011]), a costing study based on econometric modelling (n = 1 [Bahuguna et al, 2020]) and a policy/clinical review (n =1 [Singla & Singla, 2016]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaemia was found to be another important contributor to ischaemic stroke among Indians. 7 It has been reported that in some stroke patients, inflammation and immune reaction secondary to acute infection with C. pneumonia may trigger an acute stroke. 8 Alcohol abuse, clinical infection/inflammation, recreational drug abuse, psychological distress, stressful life events, birthday, negative or positive emotions, anger, heavy physical exertion, heavy eating, sudden posture change in response to a startling event have been isolated as potential triggering factors for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the third leading cause of adult disability in the world and also being the leading cause of long-term disability, it has significant disability-adjusted years of life in both developed and developing countries [1,2]. Motor impairments like hemiparesis are very common and persistent impairments in strength, balance and coordination have been associated with reduced mobility post stroke [3].…”
Section: Introductionmentioning
confidence: 99%